Psychology of the group and sport (Fiep Bulletin - online, 2015)
The literature on teddy-boys, blousons noirs halbstarkor, gamberros, teppisti, etc., which flourished 15 years ago a news curiosity or journalistic reportage, has now come into the judicious treatises of educators, sociologists, phychologists and politicians.